Nutritional Status Assessment in Cirrhotic Patients after Protein Supplementation. (4th December 2012) - Putadechakum, Supanee; Klangjareonchai, Theerawut; Soponsaritsuk, Arpussanee; Roongpisuthipong, Chulaporn
Abstract : Background . Protein supplementation has been shown to be effective for the treatment of malnourished patients with liver cirrhosis. The parameters used to assess nutritional improvement in cirrhotic patients for such treatment are important. Objective . To evaluate the parameters for assessment of nutritional status in patients with liver cirrhosis after protein supplementation. Material and Method . A cross-sectional, prospective clinical trial with 22 cirrhotic patients was performed. Data from anthropometry, bioelectrical impedance, subjective global assessment (SGA), and visceral protein were gathered and analyzed to assess nutritional improvement after protein supplementation. Results . Twenty-two cirrhotic patients (mean age 52.9 ± 12.8 years; 54.5% male; 63.6% alcoholic cirrhosis; 63.6% Child-Pugh C) were recruited. After protein supplementation, a significant improvement was demonstrated in the SGA class A from 10 patients (45.5%) to 16 (72.7%) and 18 (81.8%) at the 4th and 8th weeks, respectively. Body weight, body mass index, and lean muscle mass were significantly increased from baseline at the 8th week. No significant change in other nutritional parameters was observed. Conclusions . The SGA and lean muscle mass were significant parameters in order to assess nutritional status in cirrhotic patients after protein supplementation.